Pollen morphology and implications for the taxonomy of the genus Chrysolaena (Vernonieae, Asteraceae) - Via Do Pico, Gisela Mariel (2013)
This study aims at finding new morphological characters to evaluate the taxonomic position of species in the genus Chrysolaena (Vernonieae, Asteraceae) as suggested by the current classification of tribe Vernonieae. We characterized the morphology of pollen grains in all 18 species of Chrysolaena. Results show that all studied species possess pollen grains of type ?C?, which is therefore characteristic of the genus. This pollen type is 3-colporate, echinolophate, oblate-spheroidal, with a total of 29 lacunae, including the polar lacuna, but lacking the equatorial lacuna. Chrysolaena is considered stenopalynous due to the fact that the pollen type in most of the species is similar. Nevertheless, variation in the size of pollen grains allowed us to identify three groups of taxa: small, medium-sized and large, respectively. Pollen morphology is a useful taxonomic marker, in addition to other morphological and molecular characters defining the genus.